2022
DOI: 10.3389/fonc.2022.874645
|View full text |Cite
|
Sign up to set email alerts
|

The Status and Prospects of Epigenetics in the Treatment of Lymphoma

Abstract: The regulation of gene transcription by epigenetic modifications is closely related to many important life processes and is a hot research topic in the post-genomic era. Since the emergence of international epigenetic research in the 1990s, scientists have identified a variety of chromatin-modifying enzymes and recognition factors, and have systematically investigated their three-dimensional structures, substrate specificity, and mechanisms of enzyme activity regulation. Studies of the human tumor genome have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 185 publications
(200 reference statements)
0
6
0
Order By: Relevance
“…Given its broad regulatory effect on various processes, epigenetics was recently classified as an important hallmark of carcinogenesis. As various epigenetic alterations were reported recently in HL cells ( 66 , 67 ), it is highly likely that systematic deciphering of the role of these non-mutational changes on the genetic sequence may improve understanding of the molecular mechanisms of the development, progression and aggressiveness of this cancer type.…”
Section: Aberrant Epigenetic Mechanisms In Hlmentioning
confidence: 99%
“…Given its broad regulatory effect on various processes, epigenetics was recently classified as an important hallmark of carcinogenesis. As various epigenetic alterations were reported recently in HL cells ( 66 , 67 ), it is highly likely that systematic deciphering of the role of these non-mutational changes on the genetic sequence may improve understanding of the molecular mechanisms of the development, progression and aggressiveness of this cancer type.…”
Section: Aberrant Epigenetic Mechanisms In Hlmentioning
confidence: 99%
“…These bioinformatics targets can be found by directly affecting regulatory regions of genes, such as in the methylome or DNA methylation information sets, or by altering histone proteins and related structures. 206 The methylome can be profiled experimentally by bisulfite sequencing, while the main technique for identifying histone alteration profiles is immunoprecipitation of these proteins.…”
Section: Personalized Epigenome Targeting In Nhlmentioning
confidence: 99%
“…Understanding the genetic and epigenetic components of immune evasion is crucial. Studies on the modulation of epigenetics and immune checkpoints have shown an interaction between immune modulation and epigenetic alterations [14]. This review article provides a comprehensive summary of the latest research on the epigenetic modifications that can result in immune evasion and the development of T-cell malignancies.…”
Section: Introductionmentioning
confidence: 99%